Dale una Mano a los Bosques: Guia para Jefe de Proyecto - Alison Bowers; Janice Easton; Martha C. Monroe; Lizzie Peme; Gabriella Scollo (EDIS)
Revised! Circular 1270-S, a 74-page illustrated leader guide, is the Spanish language version of Circular 1270, "Give Forests a Hand Leader Guide" by Alison Bowers, Janice Easton, Martha C. Monroe, and Lizzie Peme, translated into Spanish by Gabriella Scollo. Published by the UF School of Forest Resources and Conservation, September 2006.